Innovative Performance via Absortive Capacity, Organizational Learning and Innovation At PT XYZ Oil and Gas Company - Agustinus, Tandiarak; Ardi, Ardi (Enrichment : Journal of Management, 2023)
One of the industrial sectors that contribute significantly to the economy in Indonesia is the oil and gas industry, mainly referred to as the upstream oil and gas industry, because of its significant contribution to gross domestic income (GDP). This research examines the influence of potential absorptive capacity, organizational learning, innovation capability, and organizational innovation on innovation performance. This research was conducted on 40 employees who worked in an oil and gas drilling company. The method used is quantitative with Structural Equation Modeling analysis techniques. The research results show that potential absorptive capacity, organizational learning, innovation capability, and organizational innovation significantly affect innovation performance. Likewise, with potential absorptive capacity, organizational learning and innovation capability influence organizational innovation